A double-blind controlled trial of etretinate (Tigason) and ibuprofen in psoriatic arthritis. Issue 3 (March 1985) - Hopkins, R; Bird, H A; Jones, H; Hill, J; Surrall, K E; Astbury, C; Miller, A; Wright, V
Abstract : Etretinate (Tigason) and ibuprofen have been compared in a double-blind controlled trial in psoriatic arthritis to see if we could confirm a specific action for this vitamin A derivative suggested from earlier uncontrolled studies. Eleven out of 20 patients completed 24 weeks of therapy with etretinate (up to 0.5 mg/kg/day) whereas only 1/20 patients completed 24 weeks of therapy with ibuprofen alone. Etretinate improved skin lesions, and this may have encouraged patients to persist with it. Improvement of statistical significance was seen for articular index in both groups. In addition significant improvement in ESR, haemoglobin, C-reactive protein, and histidine occurred in the etretinate group. The main side effects of etretinate (which may preclude its use at a higher dose in this condition) included cracked and dried lips and sore mouth.